Ownership Structure and Performance of Listed Banks in Ghana - Tuffour Maclean Amoako (KNUST, 2024)
A thesis submitted to the department of accounting and finance college of humanities and social sciences in partial fulfilment of the requirements for the degree of msc. Accounting and finance